Interferon production and lymphocyte stimulation in human leucocyte cultures stimulated by Corynebacterium parvum. - Hirt, H M (1978)
Killed C. parvum organisms stimulated a lymphoproliferative response in human peripheral leucocyte cultures of both adult and cord blood origin. They also induced high titres of interferon in cultures of adult leucocytes, but there was no correlation between the degree of lymphocyte stimulation and of interferon production. A considerable variability between donors was seen in both assays. The amount of interferon produced in C. parvum-stimulated cultures was considerably higher than that stimulated by the T-cell mitogens PHA and Con A and that induced by LPS. The anti-viral protein induced by C. parvum fulfilled the criteria of interferon and appeared to represent type II interferon.